Strength training as superior, dose-dependent and safe prevention of acute and overuse sports injuries: a systematic review, qualitative analysis and meta-analysis - Lauersen, J. P.; Andersen, T. E.; Andersen, L. B. (British Journal of Sports Medicine, 2018)
Objective This review aims to analyse strength training-based sports injury prevention randomised controlled trials (RCT) and present best evidence recommendations for athletes and future research. A priori PROSPERO registration; CRD42015006970.